Active bilayer films based on cassava starch incorporating ZnO nanorods and PVA electrospun mats containing rosemary extract. (November 2020) - Estevez-Areco, Santiago; Guz, Lucas; Candal, Roberto; Goyanes, Silvia
Abstract: Active packaging constitutes a method to preserve sensitive products (in particular foods) and extend its shelf life. In this research, a novel bilayer film with antioxidant and antimicrobial activity was developed from biodegradable polymers. The outer layer consists in a composite film of thermoplastic starch and ZnO nanorods (TPS-ZnO) obtained by flat die extrusion, and the inner layer is an electrospun mat of poly(vinyl alcohol) containing rosemary polyphenols (PVA-RE). ZnO nanorods in the outer layer inhibited the growth of Escherichia coli over its surface, while rosemary polyphenols included in PVA-RE mat showed an antioxidant activity in food simulant D1 (hydroalcoholic solution) of 33.5 μmol TE/g, as evaluated using DPPH assay. Furthermore, the PVA-RE inner layer hindered Zn(II) migration from TPS-ZnO towards food simulant D1. The addition of the PVA-RE layer onto TPS-ZnO film increased Young's modulus, stress and strain at break, and tensile toughness by 50–100% and decreased the water vapor permeability by 42% compared to TPS film. This work provides a novel approach for the developing of bi-functional active materials for advanced packaging applications. Graphical abstract: Image 1 Highlights: Active bilayer maintains the transparency of TPS film. All mechanical properties increase in more than 50% in the bilayer system. Addition of ZnO nanorods and PVA mat decrease WVP value of TPS by 42%. ZnO nanorods incorporated to TPS grant antimicrobial activity. Rosemary polyphenols in PVA nanofibers grant antioxidant activity.